2013
DOI: 10.1152/ajpheart.00080.2013
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase type 5 in cardiac disease, metabolism, and aging

Abstract: G protein-coupled receptor/adenylyl cyclase (AC)/cAMP signaling is crucial for all cellular responses to physiological and pathophysiological stimuli. There are nine isoforms of membrane-bound AC, with type 5 being one of the two major isoforms in the heart. Since the role of AC in the heart in regulating cAMP and acute changes in inotropic and chronotropic state are well known, this review will address our current understanding of the distinct regulatory role of the AC5 isoform in response to chronic stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 85 publications
1
54
0
Order By: Relevance
“…Based on experiments with AC5 knockout mice (see section II. E.3.a), it has been proposed that selective AC5 inhibition may be beneficial in the treatment of heart failure and other age-related diseases (Vatner et al, 2013;Bravo et al, 2016). However, AC5 is broadly expressed in many organs, including kidney (Erdorf and Seifert, 2011) and brain (Kim and Han, 2009), so that substantial organ toxicity could emerge as a result of global AC5 inhibition (Table 3).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on experiments with AC5 knockout mice (see section II. E.3.a), it has been proposed that selective AC5 inhibition may be beneficial in the treatment of heart failure and other age-related diseases (Vatner et al, 2013;Bravo et al, 2016). However, AC5 is broadly expressed in many organs, including kidney (Erdorf and Seifert, 2011) and brain (Kim and Han, 2009), so that substantial organ toxicity could emerge as a result of global AC5 inhibition (Table 3).…”
Section: +mentioning
confidence: 99%
“…It is particularly important to confirm that the AC inhibitor used actually prevents a GPCR-or FSKmediated cAMP increase (Brunskole Hummel et al, 2013). Because vidarabine constitutes an FDAapproved antiviral drug, the clinical use of this compound for AC5 inhibition has been proposed (Vatner et al, 2013;Bravo et al, 2016). Unfortunately, vidarabine possesses a high potential for toxic effects so that systemic clinical use would potentially be dangerous (Seifert, 2014(Seifert, , 2016.…”
Section: +mentioning
confidence: 99%
“…ADCY5 encodes adenylate cyclase 5, which catalyzes generation of cyclic AMP (cAMP) from ATP (16). cAMP, ATP, and calcium (Ca 2+ ) regulate insulin secretion in the pancreatic islet β-cell (17).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been suggested that selective AC5 inhibitors may be valuable drugs for the treatment of heart failure (Vatner et al, 2013). However, it is difficult to develop highly selective AC5 inhibitors (Braeunig et al, 2013;Brand et al, 2013;Seifert, 2014), and in the context of heart failure, additional inhibition of sGC would be detrimental for cardiovascular function (Schermuly et al, 2011;Gheorghiade et al, 2013).…”
Section: Discussionmentioning
confidence: 99%